Countervisuality in Black Resistance and Abolition of Slavery in America - Simi Nath (Innovative Research Thoughts, 2023)
This paper explores the political mobilization and Black resistance in America from 1830s to 1860 that led to abolition of slavery and seeks to link it to Nicholas Mirzeof’s idea of visuality and counter visuality. The term visuality, now a popular keyword for the study of visual culture, is redefined by Nicholas Mirzoef in his essay “The Right to Look: Counterhistory of Visuality” (2011). The term visuality is coined by Scottish historian Thomas Carlyl in 1840 to mean the “Hero’s” visualizing the history where people do not have any subjectivity but are represented. Defensive mobilization occurred among black people due to years of alienation, political exclusion and hostile racism. This defensive mobilization is a result of collective consciousness which Mirzoef calls “visual commons” – a means for social change. Black agitation for the support of abolition of slavery and freedom of African-Americans, led to an emerging leadership which can be decoded as counterheroism of what Thomas Carlyl means by the “Hero”.